Prosedur Pelayanan Telepon Operator Kepada Tamu Selama Era New Normal Di Jumana Bali Ungasan Resort - Anak Agung Istri Ratna Sari Wulan Wulan; Ni Kadek Citra; Dewa Gede Putra (Journal of Hospitality Accommodation Management (JHAM), 2022)
The goal of this study is to understand how to apply the Telephone Operator's method to guests at Hotel J Bali. The data was gathered through observation and interview. The descriptive qualitative nature of the data analysis used in this study allows us to clearly explain, lay out, and compare the information we obtained from the study documentation with the appropriate Standard Operating Procedure (SOP), from which we can draw conclusions. The analysis's findings indicate that of the 18 types of services, 10 of them adhere to the Standard Operating Procedure (SOP), while the remaining 8 do not. Suggestions for telephone operators to always come 15 minutes before work, all of them use hand gloves and faceshields when working, always ask guests to fill out complete forms, always re-check the registration form, always check room readiness, always help contact buggy and always return to tidying tables and chairs after the check-in process is complete.